2016
DOI: 10.1017/s0022215116000943
|View full text |Cite
|
Sign up to set email alerts
|

Aetiology and pathology of otitis media with effusion in adult life

Abstract: Objectives: To gather and analyse information concerning the aetiology and pathology of otitis media with effusion in adults.Method: A review of the English language literature from 1970 to the present was conducted.Results: The available evidence suggests that otitis media with effusion in adult life is best viewed as a syndrome with a number of causes, including: infiltration of the eustachian tube by nasopharyngeal carcinoma and other local malignancies; changes in the middle ear and eustachian tube induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 50 publications
2
30
0
4
Order By: Relevance
“…1 This complements nicely recent articles by Wasson and Yung 2 on the evidence-based management of otitis media (in its various forms) and the study from Dundee of sinonasal symptoms in patients with ear disease 3 which confirmed the association between the two groups of conditions. The pathology of OME in children is far from clear, and as Mills and Hathorn point out, the situation in adults is no better, with many important gaps in our knowledge.…”
supporting
confidence: 70%
“…1 This complements nicely recent articles by Wasson and Yung 2 on the evidence-based management of otitis media (in its various forms) and the study from Dundee of sinonasal symptoms in patients with ear disease 3 which confirmed the association between the two groups of conditions. The pathology of OME in children is far from clear, and as Mills and Hathorn point out, the situation in adults is no better, with many important gaps in our knowledge.…”
supporting
confidence: 70%
“…Furthermore, studies on nasal aerodynamics have shown that nasal resistance is significantly increased during nasal obstruction and that oral breathing can cause negative pressure in the nasopharynx and further negative pressure in the middle ear, which could aggravate ETD [ 27 ]. Similarly, nasal obstruction is also the most frequent nasal symptom in adult otitis media with effusion, which is considered closely related to ETD [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The optimal treatment plan is still being elucidated but currently involves topical and systemic steroids, use of antibiotics (where indicated), and in some severe cases, anti-IgE treatment such as omalizumab [30]. Control of underlying systemic pulmonary disease and/or aspirin desensitization can have a role for some patients [32,39]. Removal of polyps may be indicated in some cases but other traditional surgical approaches are unlikely to control symptoms for long.…”
Section: Treatmentmentioning
confidence: 99%